Interleukin-6 ablation does not alter morphofunctional heart characteristics but modulates physiological and inflammatory markers after strenuous exercise. (June 2021) - da Rocha, Alisson L.; Rovina, Rafael L.; Pinto, Ana P.; Marafon, Bruno B.; da Silva, Lilian E.C.M.; Simabuco, Fernando M.; Frantz, Fabiani G.; Pauli, José R.; de Moura, Leandro P.; Cintra, Dennys E.; Ropelle, Eduardo R.; Filho, Hugo T.; et al.
Abstract: Interleukin-6 (IL-6) is associated with pathological cardiac hypertrophy and can be dramatically increased in serum after an acute strenuous exercise session. However, IL-6 is also associated with the increased production and release of anti-inflammatory cytokines and the inhibition of tumor necrosis factor-alpha (TNF-α) after chronic moderate exercise. To elucidate the relevance of IL-6 in inflammatory and hypertrophic signaling in the heart in response to an acute strenuous exercise session, we combined transcriptome analysis using the BXD mice database and exercised IL-6 knockout mice (IL-6KO). Bioinformatic analysis demonstrated that low or high-levels of Il6 mRNA in the heart did not change the inflammation- and hypertrophy-related genes in BXD mice strains. On the other hand, bioinformatic analysis revealed a strong positive correlation between Il6 gene expression in skeletal muscle with inflammation-related genes in cardiac tissue in several BXD mouse strains, suggesting that skeletal muscle-derived IL-6 could alter the heart's intracellular signals, particularly the inflammatory signaling. As expected, an acute strenuous exercise session increased IL-6 levels in wild-type, but not in IL-6KO mice. Despite not showing morphofunctional differences in the heart at rest, the IL-6KO group presented a reduction in physical performance and attenuated IL-6, TNF-α, and IL-1beta kinetics in serum, as well as lower p38MAPK phosphorylation, Ampkalpha expression, and higher Acta1 and Tnf gene expressions in the left ventricle in the basal condition. In response to strenuous exercise, IL-6 ablation was linked to a reduction in the pro-inflammatory response and higher activation of classical physiological cardiac hypertrophy proteins.